A novel test device for the direct measurement of tensile strength of rock using ring shape sample. (March 2021) - Aliha, M.R.M.; Ebneabbasi, Pouyan; Karimi, Hamid reza; Nikbakht, E.
Abstract: A novel test method is proposed in this research for determining the tensile strength of rocks and geo-materials. Using a seesaw device, two diametral tensile forces are applied to the inner surface of a ring shape specimen and consequently the ring specimen is splitted along a plane normal to the direction of applied tensile loading. A suitable formulation was derived for determining the tensile strength value using the direct ring tension specimen tested with the seesaw device. The required shape factor for the suggested tensile strength relation was obtained from the finite element analyses of ring specimen with different inner and outer diameters. The practical ability of suggested direct tensile strength measurement method was examined by performing some tensile strength experiments on tuffite rock and it was found that the results obtained from this test method is in very good agreement with two other conventional indirect tensile strength testing methods namely the Brazilian disc and compressed ring tests. Suitable geometry (i.e. inner/outer diameter ratio) was also proposed for testing the ring specimen. In addition, the fracture patterns of direct and indirect ring specimens tested with different d i /d o ratios were simulated and predicted using the XFEM method.